A novel temozolomide analog, NEO212, with enhanced activity against MGMT-positive melanoma in vitro and in vivo. Issue 2 (28th March 2015) - Chen, Thomas C.; Cho, Hee-Yeon; Wang, Weijun; Nguyen, Jenny; Jhaveri, Niyati; Rosenstein-Sisson, Rachel; Hofman, Florence M.; Schönthal, Axel H.
Highlights Temozolomide was modified by conjugation to perillyl alcohol. The resulting novel analog, NEO212, exerted superior activity against melanoma. NEO212 was also active against drug-resistant tumors in vivo. NEO212 should be developed for clinical use.